Flexible Electronics: Novel Pliable Electrodes for Flexible Electrochemical Energy Storage Devices: Recent Progress and Challenges (Adv. Energy Mater. 17/2016). Issue 17 (7th September 2016) - Yousaf, Muhammad; Shi, Hao Tian H.; Wang, Yunsong; Chen, Yijun; Ma, Zhimin; Cao, Anyuan; Naguib, Hani E.; Han, Ray P. S.
Abstract : With wearable electronics becoming increasingly fashionable, flexible energy storage devices are attracting a lot of attention. Their main component, the pliable electrodes can be categorized as substrate‐supported and free‐standing. Depending on their modes of deformation they can be labeled as bendable, compressible or stretchable electrodes. In article number 1600490, Ray P. S. Han and co‐workers summarize recent progress and challenges in the design and fabrication of pliable electrodes for flexible energy storage devices.